Investigation of passive control devices to suppress acoustic instability in combustion chambers. - Avandelino Santana Junior (2008)
Combustion instability problems have been experienced during nearly every rocket engine development program, characterized by chamber pressure oscillations and high density of energy release in a volume having relatively low losses. Several distinct types of instability and their physical manifestations have been observed, although the frequency and amplitude of these oscillations and their external manifestations normally vary with the type of instability. The most destructive type of instability is referred to as high frequency instability, resonant combustion or acoustic instability, which is usually eliminated by use of passive control, involving installation of baffles, resonators, or some other modification of geometry. The main purpose of this work is the experimental investigation of use of passive control devices (Helmholtz resonators and baffles) to control acoustic instabilities in combustion chambers, because this type of instability occurs in liquid rocket engines, rocket motors and industrial burners. The first step of this research is the acoustic characterization of chamber, thus cold tests were carried out on full-scale chamber model to analyze the effects of resonators. Experimental frequency spectrum data are in excellent agreement with resonant frequencies and damping rate calculated by theoretical model, demonstrating resonators efficiency to reduce the amplitude of Sound Pressure Level at given resonant frequency. Afterwards, hot tests were carried out on burner with and without resonators, identifying the frequency spectrum of acoustic pressure in chamber, which was compared with cold tests (full-scale model) results and theory by correction factors of temperature, density, and viscosity. The experimental data validated the methodology to design resonators useable to control combustion instabilities.